Phenotypic variability of CMT4C in a French‐Canadian kindred. Issue 3 (14th May 2015) - Varley, Talia L.; Bourque, Pierre R.; Baker, Steven K.
ABSTRACT Introduction Charcot‐Marie‐Tooth type 4C (CMT4C) is an autosomal recessive dysmyelinating neuropathy characterized by precocious and rapidly progressive scoliosis. Methods Patients in a French‐Canadian kindred were evaluated with clinical examination, electrophysiologic study, and genomic DNA extraction. Results Six of 10 siblings were clinically symptomatic with supportive electrophysiologic features. The proband presented with regional side‐to‐side sensorimotor asymmetry, typical pes cavus without obvious scoliosis, and unremarkable plain films of the spine. Affected siblings all share symptoms of foot deformity but have variable onset of neuropathic symptoms, degree of extremity weakness, progression of symptoms, and, most notably, evidence of scoliosis. DNA sequence analysis revealed a novel combination of 2 known recessive mutations, p.R904X and p.R954X, in the SH3TC2 gene. Conclusions A broad spectrum of phenotypes should be considered in the possible diagnosis of CMT4C. The absence of scoliosis or late‐onset symptoms should not exclude SH3TC2 from the list of candidate genes under consideration. Age of onset and clinical features were variable and suggest that polygenic factors contribute to the final phenotype. Muscle Nerve 52:444–449, 2015